Thirty-day Outcomes of First-in-man Implantation of a Novel Transcatheter Edge-to-edge Mitral Repair System in Patients With Severe Mitral Regurgitation - Kai Xu; Yan Wang; Shaoliang Chen; Xiangbin Pan; Ben He; Ruiyan Zhang; Bin Wang; Junjie Zhang; Zhengbin Zhu; Bin Wang; Da Zhu; Yaling Han (Cardiology Discovery)
Objectives:. The aim of this multicenter, prospective, single-arm pilot study (ClinicalTrials.gov number: NCT05040074) was to observe the procedural and 30-day results of the novel transcatheter mitral valve repair system, SQ-Kyrin®-M Clip (Shenqi Medical, Shanghai, China), in patients with severe mitral regurgitation (MR). Methods:. The heart team considered patients from 5 centers in China with clinically significant functional mitral regurgitation ≥3+ despite optimal medical therapy or degenerative mitral regurgitation ≥3+ with high surgical risk as candidates for transcatheter repair. All patients received transcatheter edge-to-edge mitral valve repair under general anesthesia. The primary outcome was technical success, which included all of the following measured at the exit from the catheterization laboratory: (1) absence of procedural mortality; (2) successful access, delivery, and retrieval of the device delivery system; (3) successful deployment and correct positioning of the first intended device; and (4) no emergency surgery or reintervention related to the device or access procedure. The secondary outcomes included all-cause mortality, serious adverse events, device success, and procedural success 30 d after the intervention. Results:. From June 2021 to December 2021, 18 patients were enrolled in this study with age (75.7 ± 7.4) years. Fifteen patients had MR 4+, while 3 had MR 3+. Technical success was achieved in all patients, including 6 degenerative mitral regurgitation and 12 functional mitral regurgitation patients. There was no all-cause mortality at 30 d. One patient had single leaflet device attachment within 30 d, which was regarded as a serious adverse event, and the patient was successfully treated with reintervention by implanting another clip. Another patient’s transmitral gradient was 6 mmHg (>5 mmHg), with an effective orifice area of 2.57 cm2 after the procedure. Sixteen patients had device success and procedural success at 30 d postoperation. Fourteen patients had MR 1+, 3 had MR 2+, and only 1 patient had MR 3 + 30 d after the procedure. Conclusions:. The results of this feasibility study showed the efficacy and safety of the SQ-Kyrin®-M device in the Chinese population with severe MR, laying a solid foundation for a subsequent large-scale confirmatory study.